Адміністративно-правовий механізм забезпечення інформаційної безпеки в Україні - Перун, Тарас Степанович (Національний університет "Львівська політехніка", 2019)
У дисертації проведено комплексне дослідження адміністративно-правового механізму забезпечення інформаційної безпеки в Україні. Розглянуто інформаційну безпеку як систему суспільних відносин і об’єкт правової охорони, вихідні методологічні засади дослідження інформаційної безпеки. Проаналізовано нормативно-правове забезпечення інформаційної безпеки в Україні. Досліджено поняття та принципи побудови механізму правового регулювання забезпечення інформаційної безпеки. З’ясовано адміністративно-правове регулювання забезпечення інформаційної безпеки у контексті державного управління та державного регулювання інформаційної безпеки та систему суб’єктів її забезпечення. Здійснено аналіз особливостей адміністративно-правового режиму забезпечення інформаційної безпеки. Окреслено шляхи підвищення ефективності адміністративно-правового механізму забезпечення інформаційної безпеки в Україні. В диссертации проведено комплексное исследование административно-правового механизма обеспечения информационной безопасности в Украине. Рассмотрены информационная безопасность как системы общественных отношений и объект правовой охраны, исходные методологические основы исследования информационной безопасности. Проанализировано нормативно-правовое обеспечение информационной безопасности в Украине. Исследовано понятие и принципы построения механизма правового обеспечения информационной безопасности. Выяснено административно-правовое регулирование обеспечения информационной безопасности в контексте государственного управления и государственного регулирования информационной безопасности и систему субъектов ее обеспечения. Осуществлен анализ особенностей административно-правового режима обеспечения информационной безопасности. Определены пути повышения эффективности административно-правового механизма обеспечения информационной безопасности в Украине. The dissertation analyzes the administrative and legal mechanism of ensuring information security in Ukraine. The scientific approach is substantiated, which assumes that under information security, in the conditions of development of information society and aggression in the east of Ukraine, the state of security of information resources, databases, information technologies and technical means intended for gathering, processing, storage and transfer of information necessary is understood. to realize the rights and legitimate interests of information subjects, persons, society and the state in the information space from the influence of a specific type of threats, which appear in the form of purposeful Language not or spontaneous activity in the information environment. It is argued that information security acts as an object of legal protection. Legal means of ensuring information security are a leading factor in the protection of national interests, and their application is determined by: optimizing the balance of relations between the right of information relations subjects to receive information and the right to set restrictions on these relations by other persons with regard to the information they own. It is stated that from the standpoint of the methodology of law, the paradigm of information security has a structure, which is formed by: the methodology of law enforcement, legislation of Ukraine, systematic of administrative law, norms of administrative law, administrative-legal relations, legal qualification of administrative-legal relations, interpretation of rules of law, mechanism of application of law, state legal policy in the field of information security, culture and ethics of the application of the legislation that establishes restrictions on human rights and freedoms, strategy and tact and the activities of information security entities. It is emphasized that the mechanism of right regulation is a system of special legal means, organized in a consistent way, aimed at regulating social relations of a certain kind. The design of a mechanism for the legal regulation of information security should be carried out in accordance with the purpose of the legal regulation. It is substantiated that the system of information security entities is a complete set of elements that are in the defined functions of information security of public relations, united by the sphere of interests and needs, reflecting the legal characteristics of administrative and legal means of regulation, content and elements of the legal status of sub entities that participate in relationships governed by information law, systemic in content. It is stated that the peculiarity of organizational and legal support of the administrative and legal regime of information security determines the application of technical standards of information security adopted in the EU and NATO, which are formulated as a result of the identification of typical legal cases and the unification of technical and legal norms that regulate the order of activity of entities providing information security. security, in the context of relations arising from administrative and other public relations, with a view to focusing the provisions on the equality of fools in addressing threats in information and telecommunication systems and in the national information space. It is shown that the peculiarities of administrative and legal regimes for ensuring information security are revealed through the mechanism of self-regulation with the participation of public-legal entities, establishing a balance of interests. Improving the effectiveness of the legal regulation of information security is impossible without reliance on a theoretical foundation, the formation of which, in turn, must take into account the substantive foundations of the legal idea, the essence of which is the indissoluble unity of ideas of independence, territorial integrity and sovereignty, justice and national interest, possible and national interest. implementation of a set of legal measures to which they relate: a clear reflection in the law and state institutions of the orientation on the combination of public and private economic interests in the information sphere; continuous and consistent use of human rights mechanisms and procedures for overcoming conflicts in the information sphere; raising the legal level of consciousness and activity of representatives of all branches and levels of government, the population of the country.
Административно-правовой механизм обеспечения информационной безопасности в Украине
Administrative and legal mechanism of information security in Ukraine
Keywords: інформаційна безпека; адміністративно-правовий механізм; суб’єкти забезпечення інформаційної безпеки; правові норми; інформаційні технології; критично важлива інформаційна інфраструктура; информационная безопасность; административно-правовой механизм; субъекты обеспечения информационной безопасности; правовые нормы; информационные технологии; критически важна информационная инфраструктуры; information security; administrative and legal mechanism; subjects of providing information security; legal norms; information technologies; critical information infrastructure; 342.6:342.922(477)